Assessing groundwater artificial recharge suitability in the Mi River basin using GIS, RS, and FAHP: a comprehensive analysis with seasonal variations - Qianyu Song; Yuyu Liu; Zhongpeng Wang; Zhenghe Xu (Applied Water Science)
Abstract The escalating depletion and irrational exploitation of global groundwater resources have led to severe ecological and environmental repercussions and exacerbated water scarcity. Therefore, effective, sustainable management remains urgent to ensure the security and balance of water resources. This study utilized an integrated approach that combines Geographic information systems (GIS), remote sensing, and the fuzzy analytic hierarchy process to assess the suitability of artificial recharge in the Mi River watershed, creating 14 thematic layers. FAHP is a crucial tool for assigning relative weights to these layers, enabling a comprehensive assessment of the suitability of artificial recharge. The study area was categorized into five suitability classes with notable seasonal variations. During the wet season, the areas were rated as follows: 5.80%, very good; 35.24%, good; 41.96%, moderate; 16.11%, poor; 0.89%, very poor. These percentages during the dry season changed to 11.02% (very good), 39.80% (good), 34.39% (moderate), 10.39% (poor), and 4.39% (very poor). The central basin regions were deemed less suitable for artificial recharge. The model's accuracy was validated by analyzing receiver operating characteristic curves derived from a dataset of 29 wells. This study provides a scientific foundation for sustainable groundwater management within the Mi River watershed and substantiates the effectiveness of GIS and FAHP in evaluating artificial recharge potential. Future research should improve data accuracy to increase model precision and extend its applicability to various geographical and environmental settings.